2004
DOI: 10.1038/nrn1535
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal signalling of fear memory

Abstract: The learning and remembering of fearful events depends on the integrity of the amygdala, but how are fear memories represented in the activity of amygdala neurons? Here, we review recent electrophysiological studies indicating that neurons in the lateral amygdala encode aversive memories during the acquisition and extinction of Pavlovian fear conditioning. Studies that combine unit recording with brain lesions and pharmacological inactivation provide evidence that the lateral amygdala is a crucial locus of fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
999
4
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,313 publications
(1,073 citation statements)
references
References 105 publications
49
999
4
8
Order By: Relevance
“…Abnormally high psychophysiological conditioned responses to reminders of traumatic events can persist as long as 50 years following its cessation (Orr et al, 1993). These data suggest that a deficit in either extinction learning or retention of that learning may underlie failure to recover from the effects of the traumatic stressor (Rauch et al, 2006;Milad et al, 2006b;Davis et al, 2006;SotresBayon et al, 2004;Maren and Quirk, 2004). Consistent with this view, slower extinction of corrugator electromyogram responses were found to represent a pre-trauma risk factor for PTSD-related symptoms following a traumatic event (Guthrie and Bryant, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Abnormally high psychophysiological conditioned responses to reminders of traumatic events can persist as long as 50 years following its cessation (Orr et al, 1993). These data suggest that a deficit in either extinction learning or retention of that learning may underlie failure to recover from the effects of the traumatic stressor (Rauch et al, 2006;Milad et al, 2006b;Davis et al, 2006;SotresBayon et al, 2004;Maren and Quirk, 2004). Consistent with this view, slower extinction of corrugator electromyogram responses were found to represent a pre-trauma risk factor for PTSD-related symptoms following a traumatic event (Guthrie and Bryant, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…The infralimbic medial prefrontal cortex (IL) and basolateral amygdala (BLA) are implicated in acquisition of conditioned fear responses [102]. Moreover, plasticity in these regions is believed to mediate reversal of conditioned fear responses with extinction [103,104]. Peña et al [101] hypothesized that VNS may alter the strength of connections between these areas to enhance the extinction of fear.…”
Section: Preclinical Studies For Post-traumatic Stress Disordermentioning
confidence: 99%
“…Taken together, these previous results suggested that NMDARs in the amygdala are involved in the retention/ consolidation of the long-term extinction memory, but not its initial acquisition (Maren and Quirk, 2004). However, the results are inconclusive, because side effects of the two drugs used to block NMDARs may have interfered with assessment of extinction acquisition during the training session.…”
Section: Introductionmentioning
confidence: 95%
“…Current models for fear extinction propose interactions between the amygdala, medial prefrontal cortex, and hippocampus (Maren and Quirk, 2004;Sotres-Bayon et al, 2004. Understanding the phase of learning and memory (acquisition, consolidation, retention, retrieval) during which each structure participates in extinction will provide a deeper understanding of the mechanisms involved and may lead to better ways to treat fear and anxiety disorders.…”
Section: Lateral Amygdala In the Acquisition Of Fear Extinctionmentioning
confidence: 99%
See 1 more Smart Citation